Ultrasound-guided angioplasty, a suitable alternative in some patients - Marques,Maria Guedes (2015)
Introduction and Objectives: Percutaneous transluminal angioplasty has been the central therapeutic modality used to treat dialysis vascular access (VA) dysfunction. The gold standard imaging modality is digital subtraction angiography. Some centers recently reported their technical success with ultrasound-guided angioplasty. Material and Methods: The authors report their first case experience with this modality. A 73 -year -old, diabetic male, on hemodialysis through a brachiocephalic fistula for 4 years, was referred to consultation due to increase of aneurisms, prolongation of haemostasis, recirculation increase and access blood flow (ABF) decrease > 25% from the baseline (1300 ml/min). Regarding the patients history, there was a mild degree of steal syndrome after the fistula surgery, which improved over time. Doppler ultrasound was successfully used to evaluate VA, characterize stenosis, and guide endovascular procedure. Results: Three haemodynamic significant stenosis were diagnosed; BF 650 ml/min; resistance index 0.62. The guidance of an eight mm diameter angioplasty balloon allowed a successful dilation of the stenoses. The first angioplasty was performed in the cephalic arch stenosis, which increased the ABF to 802 ml/min. Then, the middle stenosis was dilated with a post -procedure ABF of 930 ml/min. Finally, the post -aneurism stenosis was also dilated with a final result of 1195 ml/min, and clinical improvement without any sign of steal syndrome recurrence or procedure-related complications. Monitoring and surveillance after first trimester show a well-functioning fistula with stable flow rates. Conclusion: Doppler ultrasound has a key role in the VA surveillance, because it is the only exam that bases decisions on a morphologic and haemodynamic assessment. More than a diagnostic exam, ultrasound guidance may provide a valid and safe tool in the treatment of peripheral VA stenosis. Main advantages of this modality include lack of radiation and contrast; lower costs; and possible future procedures in the dialysis chair. Furthermore, patients with high risk of steal syndrome or heart failure would benefit from a controlled procedure with real time evaluation, not only based on their anatomy, but mainly on haemodynamic features.